Simulation-Based Voltage Drop Mitigation in a 20 kV Distribution Network Using Conductor Uprating Base on ETAP 12.6 - Turahma, Anisya; Fadhillah, Nailul; Samsurizal, Samsurizal (Institute Of Advanced Knowledge and Science, 2025)
At PT PLN (Persero) UP3 Palembang, especially the Kenten area in the feeder distribution system, there has been a drop voltage and is almost close to the applicable standard threshold. So preventive efforts are needed so that the drop voltage situation does not worsen. It was recorded that there had been the highest drop voltage in the Beo feeder by 3.05%, in the Kacer feeder by 2.6%, the Pipit feeder by 2.35%, the Merak feeder by 2.3%, and the Foil feeder by 2.3%. This is a problem that should be able to be improved. In this study, a simulation of drop voltage repair will be carried out with the help of ETAP 12.6 software, which will describe a single line diagram with the results of load flow analysis in the form of drops that occur, with the authenticity of the data obtained as the simulation results show the real state of the field. In the simulation of repairing the drop voltage using the Conductor Uprating method for the repair of the drop that occurred in the feeder, after the repair was made, the drop voltage that occurred decreased in the Beo feeder by 1.705%, in the Kacer feeder by 1.69%, the Pipit feeder by 1.48%, the Merak feeder by 1.315%, and the Foil feeder by 1.24%.